Parties, Term Limits, and Representation in the U.S. States. (January 2014) - Clark, Jennifer Hayes; Williams, R. Lucas
This research examines how severing the electoral connection influences legislative behavior. Unlike previous studies of legislative shirking, we argue for a more nuanced conceptualization that takes account of members' electoral circumstances (beyond a dichotomous measure of term limited/nonterm limited) as well as the nature of the votes under consideration. This enables us to incorporate expectations of party influence into our model of legislative shirking. Our research demonstrates shirking among legislators leaving public office as they are no longer susceptible to party pressure, while those who face term limits and are seeking another public office may remain adherent to the party on votes most crucial to the party (i.e., procedural votes). Moreover, we find evidence that legislators who are no longer constrained by elections also exhibit a greater level of roll call abstention, although only those leaving public office demonstrate significant increases in abstentions on procedural votes. Thus, we may find very different shirking patterns among term-limited members depending on their future political ambition (or lack thereof) and also depending on the nature of the votes that we are examining.